Factors contributing to differences in unmet healthcare needs among vietnamese older persons between pre- and post-covid-19 pandemic periods: Evidence from national surveys - Thuy Tien Ngoc Doan; Long Thanh Giang (Asian Development Bank Institute (ADBI), 2024)
Unmet healthcare needs refer to the situation when individuals fail to use healthcare services identified as a necessity to avoid any health consequences. The COVID-19 pandemic imposed additional challenges for older persons in addressing their healthcare needs, especially in the context of social distancing or curfew. To the best of our knowledge, this is the first study to explore the differences in unmet healthcare needs between the pre-COVID-19 (in 2019) and post-COVID-19 (in 2022) periods in Viet Nam. This study, using two nationally representative surveys, aimed to assess the changes in unmet healthcare needs (including inpatient and outpatient healthcare) among Vietnamese older persons between these time points, and to quantify the factors contributing to these changes. The Blinder-Oaxaca decomposition method was applied to explore various demographic, socioeconomic, and health factors. Educational levels, social participation, and cognitive and remembering impairments were found to be statistically significant factors. As unmet healthcare needs leave older persons with serious health consequences, it is important to determine factors attenuating such unmet healthcare needs in order to propose appropriate interventions and policies to protect this vulnerable population.
Keywords: I12; I14; I15; I18; J14; P46; 330; healthcare services; unmet healthcare needs; Blinder-Oaxaca decomposition; older persons; Viet Nam